Telomeres, tethers and trypanosomes - Field, Mark C. (Landes Bioscience, 2012)
Temporal and spatial organization of the nucleus is critical for the control of transcription, mRNA processing and the assembly of ribosomes. This includes the occupancy of specific territories by mammalian chromosomes, the presence of subnuclear compartments such as the nucleolus and Cajal bodies and the division of chromatin between active and inactive states. These latter are commonly associated with the location of DNA within euchromatin and heterochromatin respectively; critically these distinctions arise through modifications to chromatin-associated proteins, including histones, as well as the preferential localization of heterochromatin at the nuclear periphery. Most research on nuclear organization has focused on metazoa and fungi; however, recent technical advances have made more divergent eukaryotes accessible to study, with some surprising results. For example, the organization of heterochromatin is mediated in metazoan nuclei in large part by lamins, the prototypical intermediate filament proteins. Despite the presence of heterochromatin, detected both biochemically and by EM in most eukaryotic organisms, until this year lamins were thought to be restricted to metazoan taxa, and the proteins comprising the lamina in other lineages were unknown. Recent work indicates the presence of lamin orthologs in amoeba, while trypanosomatids possess a large coiled-coil protein, NUP-1, that performs functions analogous to lamins. These data indicate that the presence of a nuclear lamina is substantially more widespread than previously thought, with major implications for the evolution of eukaryotic gene expression mechanisms. We discuss these and other recent findings on the organization of nuclei in diverse organisms, and the implications of these findings for the evolutionary origin of eukaryotes.